Neuroimaging research progress of acupuncture treatment for patients with functional dyspepsia - He, Yu-Qi; Zhang, Pan; Mao, Yang-Ke; Li, Si-Yang; Zeng, Fang; Yin, Tao (Zhēncì yánjiū, 2024)
Neuroimaging technology provides objective and visualized research tool to study the mechanisms of acupuncture effects. Building on a systematic review of previous clinical studies on acupuncture treatment for functional dyspepsia using neuroimaging technology, this paper summarizes and synthesizes past researches from 4 aspects： acupoint-specific effects, factors influencing the effects, different physiological responses, and predictive factors for acupuncture efficacy. It suggests that acupuncture treatment for FD involves central integration with disease-targeted (acupuncture treatment can target and regulate abnormal brain functional activity patterns in patients with FD), meridian-specific (stimulation of specific acupuncture points along the stomach meridian can significantly regulate abnormal brain functional activity patterns in FD patients), and dynamic conditional features(the effects of acupuncture treatment for FD are influenced by multiple factors). Lastly, considering the current research status, this paper outlines prospects in terms of research subjects, influencing factors, and result validation, aiming to provide references for future in-depth research.